200k views
2 votes
Hello everyone!
Question is in the attachment!
Concept : Straight lines​

Hello everyone! Question is in the attachment! Concept : Straight lines​-example-1
User Key
by
5.0k points

2 Answers

3 votes

Explanation:

hope it helps you

thank you

Hello everyone! Question is in the attachment! Concept : Straight lines​-example-1
Hello everyone! Question is in the attachment! Concept : Straight lines​-example-2
Hello everyone! Question is in the attachment! Concept : Straight lines​-example-3
User Yousaf
by
5.4k points
2 votes

Concept :

- To solve this question we will assume the vertices to be P(3,4) and Q(-2,3) and R(x,y)

- All the sides in an equilateral triangle are equal. Therefore PQ = PR = QR, we will find distance between them by using the distance formula

- Then we will equate PR = QR to form an equation in 2 variables [1] after this we will equate PR = PQ and will substitute the value of y from the above equation [1] to get a quadratic equation in one variable, and will solve it! :D

Distance formula =
\sf \sqrt{ {( x_2 - x_1)}^(2) + {(y_2 - y_1)}^(2)}

Solution :

Let, the coordinates of vertices of the equilateral triangle be P(3,4) and Q(-2,3) and R(x,y)

Also, PQ = PR = QR

Finding PQ using distance formula,


x_(2) = -2


x_(1) = 3


y_(2) = 3


y_(1) = 4

Putting the values,


\begin{gathered} \sf PQ = \sqrt{ {( - 2 - 3)}^(2) + {(3- 4)}^(2)} \end{gathered}


\sf PQ = \sqrt{ {( - 5)}^(2) + {( - 1)}^(2)}


\sf PQ = √( 25 + 1)


\sf PQ = √( 26)

Finding PR using distance formula,


x_(2) = x


x_(1) = 3


y_(2) = y


y_(1) = 4

Putting the values,


\begin{gathered} \sf PR = \sqrt{ {( x - 3)}^(2) + {( y - 4)}^(2)} \end{gathered}

Using (a - b)² = a² + b² - 2ab


\begin{gathered} \sf PR = \sqrt{ {x}^(2) + { (3)}^(2) - 2(x)( 3)+ {y}^(2) + { (4)}^(2) - 2(y)( 4)} \end{gathered}


\begin{gathered} \sf PR = \sqrt{ {x}^(2) + 9 - 6x+ {y}^(2) + 16 - 8y} \end{gathered}


\begin{gathered} \sf PR = \sqrt{ {x}^(2) + {y}^(2) - 6x - 8y + 25} \end{gathered}

Finding QR using distance formula,


x_(2) = x


x_(1) = -2


y_(2) = y


y_(1) = 3


\begin{gathered} \sf QR = \sqrt{ {( x - (- 2))}^(2) + {( y - 3)}^(2)} \end{gathered}


\begin{gathered} \sf QR = \sqrt{ {( x + 2)}^(2) + {( y - 3)}^(2)} \end{gathered}

Using (a - b)² = a² + b² - 2ab and (a + b)² = a² + b² + 2ab


\begin{gathered} \sf QR = \sqrt{ {x}^(2) + {(2)}^(2) + 2(x)(2) + {y}^(2) + {(3)}^(2) - 2(y)(3)} \end{gathered}


\begin{gathered} \sf QR = \sqrt{ {x}^(2) + 4 + 4x + {y}^(2) + 9 - 6y} \end{gathered}


\begin{gathered} \sf QR = \sqrt{ {x}^(2) + {y}^(2) + 4x- 6y + 13} \end{gathered}

Now, PR = QR


\begin{gathered} \sf \sqrt{ {x}^(2) + {y}^(2) - 6x - 8y + 25} = \sqrt{ {x}^(2) + {y}^(2) + 4x- 6y + 13} \end{gathered}

By squaring both sides, the root will get cancel


\begin{gathered} \sf \cancel{ {x}^(2)} + \cancel{{y}^(2) } - 6x - 8y + 25 = \cancel{ {x}^(2)} + \cancel{{y}^(2) } + 4x- 6y + 13 \end{gathered}


\begin{gathered} \sf - 10x - 2y + 12 = 0 \end{gathered}


\begin{gathered} \sf - 5x - y + 6 = 0 \end{gathered}


\begin{gathered} \sf 6 - 5x = y \: \: (1)\end{gathered}

Also PR = PQ


\begin{gathered} \sf \sqrt{ {x}^(2) + {y}^(2) - 6x - 8y + 25} \sf = √( 26)\end{gathered}

By squaring both sides, the root will get cancel


\begin{gathered} \sf {x}^(2) + {y}^(2) - 6x - 8y \sf = 26 - 25\end{gathered}


\begin{gathered} \sf {x}^(2) + {y}^(2) - 6x - 8y \sf = 1\end{gathered}

Put value of y from equation (1)


\begin{gathered} \sf {x}^(2) + { (6 - 5x)}^(2) - 6x - 8( 6 - 5x) \sf = 1\end{gathered}

Using (a - b)² = a² + b² - 2ab


\begin{gathered} \sf {x}^(2) +25 {x}^(2) + 36 - 2(6)(5x) - 6x - 48+ 40x \sf = 1\end{gathered}


\begin{gathered} \sf {x}^(2) +25 {x}^(2) + 36 - 60x - 6x - 48+ 40x \sf = 1\end{gathered}


\begin{gathered} \sf 26 {x}^(2) - 26x - 12 \sf = 1\end{gathered}


\begin{gathered} \sf 26 {x}^(2) - 26x - 13 \sf =0 \end{gathered}


\begin{gathered} \sf 2 {x}^(2) - 2x - 1 \sf =0 \end{gathered}

Using quadratic formula to solve the quartic equation,


\begin{gathered} \sf x = \frac{ - b \pm \sqrt{ {b}^(2) - 4(a)(c)} }{2a} \end{gathered}


\begin{gathered} \sf x = \frac{ - ( - 2) \pm \sqrt{ {( - 2)}^(2) - 4(2)( - 1)} }{4} \end{gathered}


\begin{gathered} \sf x = (2 \pm √( 4 + 8) )/(4) \end{gathered}


\begin{gathered} \sf x = (2 \pm √( 12) )/(4) \end{gathered}


\begin{gathered} \sf x = (2 \pm √( 2 * 2 * 3) )/(4) \end{gathered}


\begin{gathered} \sf x = (2 \pm 2√( 3) )/(4) \end{gathered}


\begin{gathered} \sf x = (2(1 \pm √( 3) ))/(4) \end{gathered}


\begin{gathered} \sf x = (1 \pm √( 3) )/(2) \: \: (2)\end{gathered}

Put value of x in equation (1)


\begin{gathered} \sf 6 - 5((1 \pm √( 3) )/(2)) = y \end{gathered}


\begin{gathered} \sf (12 - 5 ( 1 \pm √( 3)) )/(2) = y \end{gathered}


\sf (7 \mp 5 √( 3) )/(2) = y

The coordinates of third vertex is
\sf ( (1 + √(3) )/(2) ) , ( (7 - 5 √(3) )/(2) ) or
\sf ( (1 - √(3) )/(2) ) , ( (7 + 5 √(3) )/(2) )

Correct Answer is - Option (b)! :)

User Roger Sanders
by
6.1k points